Determinants of pollution abatement and control expenditure: evidence from Romania - Guglielmo Maria Caporale; Christophe Rault; Robert Sova; Anamaria Sova (Institute for the Study of Labor (IZA), 2008)
The aim of the present study is to shed some light on the factors affecting Pollution Abatement and Control Expenditure (PACE) in the context of a transition economy such as Romania, in contrast to the existing literature which mostly focuses on developed economies. Specifically, we use survey data of the Romanian National Institute of Statistics and estimate Multilevel Regression Model (MRM) to investigate the determinants of environmental behaviour at plant level. Our results reveal some important differences vis-à-vis the developed countries, such as a less significant role for collective action and environmental taxes, which suggests some possible policy changes to achieve better environmental outcomes.
urn:nbn:de:101:1-20081126470
Keywords: Q52; 330; Pollution abatement and control expenditure; transition economy; Multilevel Regression Model (MRM); Umweltmanagement; Umweltschutzkosten; Kontrolle; Systemtransformation; Rumänien